The architecture of functional lateralisation and its relationship to callosal connectivity in the human brain - Vyacheslav R. Karolis (Nature Portfolio, 2019)
Many functions of the human brain are lateralised i.e. associated more strongly with either the left or the right hemisphere of the brain. Here, the authors report the first complete map of functional asymmetries in the human brain, and its relationship with structural inter-hemispheric connectivity.